Performance Comparison between Neutralization Tailings and Flotation Tailings Used for Backfill Mix and Mechanism Analysis - Bin Han; Wei Sun; Shaofeng Yu; Chao Liu; Song Yao; Jianxun Wu (Advances in Materials Science and Engineering)
A comparison test of different tailings used for underground backfill was conducted, using neutralized tailings from BIOX and flotation tailings of Jinfeng Mine. Laboratory comparison test results show that, with neutralized tailings, when the cement dosage is at 19%, backfill UCS after 7 days, 14 days, and 28 days are 105%–163%, 80%–102%, and 33%–43%, respectively, which are higher than those of flotation tailings. When the cement dosage is at 12%, backfill UCS after 7 days, 14 days, and 28 days are 58%–77%, 50%–60%, and 28%–51%, respectively, which are higher than those of flotation tailings. Slurry fluidity of neutralized tailings is lower than that of flotation tailings, while, in these two tailings, the difference of slump and diffusivity values is less than 6%, which is not a significant difference in slurry fluidity. The reason for neutralized tailings showing higher UCS is as follows: during backfill curing, neutralization tailings produce abundant crystals of CaSO4·2H2O in interlaced structure which helps in combining aggregates closely; CaSO4·2H2O hydrates with C3A C4AF contained in the cement and forms clavate cement bacillus which works as a micro reinforcing steel bar. The test proved that neutralized tailings are more optimal for backfilling.